Análise da insegurança na percepção dos sojicultores quanto aos contratos de venda antecipada da commodity soja - Junges, Camila Gabriela (2023)
The empowerment of agribusiness in Brazil’s Gross Domestic Product, even after the Covid-19 pandemic, reinforces the need for constant study of the nuances of the activity. The agricultural commodity soybean, over the past harvests, has experienced price appreciation but still faces production problems due to adverse climatic events, raising doubts about the best commercialization methods for rural producers. In this regard, commercialization through pre-sale contracts, also known as soybean anticipated sale contracts, became the subject of study in this dissertation. The methodology adopted was based on the application of questionnaires to soybean producers in the region of Toledo/Paraná, from the perspective of the assumptions of the New Institutional Economics and the Transaction Cost Economics, with a legal approach to the structure of governance in business contracts. The approach used in the field research was qualitative, focusing on the 2021/2022 harvest. The research problem consisted of investigating whether there is insecurity among soybean producers in using pre-sale contracts as a way of commercializing their production. Although these contracts present certain advantages, the study observed that there is insecurity when it comes to using this instrument, demonstrating a decline compared between 2020/21 and the 2021/22 harvests.